2011
DOI: 10.3892/ijmm.2011.774
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of PDX1 gene-modified human umbilical cord mesenchymal stem cells into insulin-producing cells in vitro

Abstract: Abstract. Mesenchymal stem cells (MSCs) have significant advantages over other stem cell types, and greater potential for immediate clinical application. MSCs would be an interesting cellular source for treatment of type 1 diabetes. In this study, MSCs from human umbilical cord were differentiated into functional insulin-producing cells in vitro by introduction of the pancreatic and duodenal homeobox factor 1 (PDX1) and in the presence of induction factors. The expressions of cell surface antigens were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…On the other hand, brown adipocytes have hypomethylated exonic regions that are significantly enriched for genes involved in brown fat functions such as the mitochondrial respiratory chain and fatty acid oxidation [25]. Notably, several Hox transcription factors are differentially methylated, some of which are linked to adipogenesis and diabetes [26,27]. For example, Hoxc9 is a well-established adipocyte marker [28], and Hoxc9 and Hoxc10 promoter methylation is inversely correlated with their gene expression in brown adipose tissue.…”
Section: Dna (De)methylation In Brown Adipogenesismentioning
confidence: 99%
“…On the other hand, brown adipocytes have hypomethylated exonic regions that are significantly enriched for genes involved in brown fat functions such as the mitochondrial respiratory chain and fatty acid oxidation [25]. Notably, several Hox transcription factors are differentially methylated, some of which are linked to adipogenesis and diabetes [26,27]. For example, Hoxc9 is a well-established adipocyte marker [28], and Hoxc9 and Hoxc10 promoter methylation is inversely correlated with their gene expression in brown adipose tissue.…”
Section: Dna (De)methylation In Brown Adipogenesismentioning
confidence: 99%
“…They also showed that β-cell related genes were expressed in both differentiated cells and β-like cells transplanted in to the liver of STZ-induced diabetic rats through portal vein. As a result blood glucose levels were significantly reduced 4weeks after transplantation (He et al, 2011). The differentiated IPCs from human WJ-MSCs could alleviate hyperglycemia in diabetic mice (Tsai et al, 2012).…”
Section: Mscs From Wharton's Jellymentioning
confidence: 98%
“…Expression of insulin Secretion of C-peptide Expression of pancreas-specific genes (Hashemian et al,2015) Correspondence to high concentrations of glucose (Wu et al, 2009) Reduction of blood glucose levels after 4weeks of transplantation (He et al,2011) (Hashemian et al, 2015). …”
Section: Wj-mscsmentioning
confidence: 99%
“…Another group managed to differentiate WJ-MSCs into insulin-producing cells in vitro [12]. Other groups reported the differentiation of WJ-MSCs into insulin-producing cells with islet-like morphology, using recombinant adenovirus– PDX1 gene constructs [13, 14]. Despite showing positive indications toward DE differentiation, these studies reported the use of animal serum and/or genetic modifications, and resulted in low differentiation capacities.…”
Section: Introductionmentioning
confidence: 99%